Acquired aplastic anaemia after SARS-CoV-2 infection in China: a case report - Xiyan Wu; Yi Mo; Kailiang Wen; Rui Ming; Xinyu Yin; Liang Hu; Gang Liu; Ge Lin; Weina Li; Weina Li; Weina Li (Frontiers Media S.A., 2023)
Since the coronavirus disease 2019 (COVID-19) pandemic began, several research groups in different countries have described cases of aplastic anaemia (AA) after COVID-19 or COVID-19 vaccination. Here, we present the case of a patient with new-onset AA in Changsha, China, that was presumably associated with preceding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. We conducted an epidemiological assessment of the incidence rate of blood system diseases from July 1, 2022, to May 31, 2023, in the haematology department of the Second Xiangya Hospital of Central South University and Hunan Children's Hospital. The detection rates of AA and leukaemia in the first two months after the epidemic outbreak were higher than those before and during the outbreak. However, only the difference in the detection rate of leukaemia was statistically significant.